Effect of Salvadora persica chewing sticks on maxillary central incisors crown-root angulation in Western-Asian population & correlation with Collum angle on 3D CBCT images - Zeeshan, Tayyaba; Qamar, Zeeshan; Bamousa, Badr; Al-Thunian, Felwah Fahad; Alwaqdani, Helayel; Alhumaidi, Abdulrahman; Alkhadra, Adel; Banaeem, Abdullah (Edelweiss Applied Science and Technology, 2024)
The main aim of the study was to identify the Collum angle classification for maxillary central incisors among individuals use vs not-use chewing sticks which could have beneficial role for immediate implant placement in respective individuals. Additionally, to identify the root-crown positioning and angulation in the Western Asian Saudi Arabian population for chewing sticks user’s vs non-users in order to develop guideline for the prosthetic procedures using Cone beam computed tompography (CBCT). A total number of 380 CBCT scans were included in the study for both of the groups based on the inclusion criterion of the patients reporting to the Dental OPD of Riyadh Elm University. The data was analyzed using 3D planner dental imaging software. Initially the teeth were classified based on root position in relation to facial plate of alveolar bone using Jung et al. classification. Additionally, the Collum angle and the root angulation of the maxillary central incisors was evaluated. The data was analyzed using one-way Anova with post-hoc Tuckey-Kramer test for pair-wise comparison. As per the Jung et al. classification, majority of the roots were observed with buccal placement. Based on the Collum angle classification majority of the maxillary central incisors were observed with facial placement (n=170), specially subtype I (n=78). But the root angulation was observed to be independent of Collum angle. Thus, it can be concluded, unlike root angulation, Collum angle has a correlation with root positioning. The angle for the individuals using chewing sticks of Salvadora Persica was similar to the individuals not using the miswak. Collum angle is correlated in all classified position of root. But the root angulation is independent of classification varies between miswak and non-miswak users.